Hypnobirthing Dan Penurunan Kecemasan Ibu Hamil Trimester III Literature Review - Fariha Hinisa; Yessy Octa Fristika (STIKes Budi Mulia Sriwijaya, 2025)
During pregnancy, there are physical and psychological changes that occur in the mother. Fear starts to arise in the third trimester. Pregnant women begin to feel anxious about the baby's well-being and their own, such as concerns about the baby being born with abnormalities, the process of childbirth, and delivery. This anxiety can trigger uterine contractions that may result in preterm birth, miscarriage, and depression. Furthermore, these conditions can increase blood pressure, leading to preeclampsia and miscarriage. Many pregnant women employ various methods to reduce their anxiety, one of which is relaxation techniques or self hypnosis. Hypnobirthing is a self-hypnosis technique, a natural effort to implant positive intentions/suggestions from the subconscious mind during pregnancy.Objective: To determine the role of hypnobirthing technique in reducing anxiety in pregnant women.Method: A literature review was conducted on the Google Scholar database between 2016 and 2024, focusing specifically on the effects of hypnobirthing technique in reducing anxiety in pregnant women. The results will be determined through the literature review.Results: Hypnobirthing technique has been proven effective in reducing anxiety and distress in pregnant women in the third trimester.Conclusion: Hypnobirthing technique is one approach that can reduce anxiety in pregnant women in the third trimester as it has a positive impact on childbirth preparation, helping mothers feel calmer, prepared, and confident in facing the labor process.